Invasive Subacute Pulmonary Aspergillosis After Puerperal Sepsis: Case Report - Killen H. Briones-Claudett MSc, MD; Mónica H. Briones-Claudett MSc, MD; Roger Alexander Murillo Vasconez MD; María F. Alfonzo Pacheco MD; Eduardo Andres Martinez Armijo MD; Killen H. Briones Zamora MS; Diana C. Briones Marquez MS, MD; Diana Franco Chávez MD; Michelle Grunauer MD, PhD (SAGE Publishing, 2020)
Subacute invasive aspergillosis is an infection that locally destroys lung parenchyma, and it affects patients with mild immunocompromise. The diagnosis is made by clinical symptoms, imaging, and laboratory results related to the infection. Early diagnosis and treatment is imperative for a favorable patient outcome. In this article, we present the case of a 19-year-old woman who was admitted to the intensive care unit for puerperal sepsis where a hysterectomy was performed. During her hospitalization, she presented atelectasis of the left lung and hemodynamic instability. Chest X-ray and chest computed tomography scan were performed and showed round opacities. It was decided to perform flexible bronchoscopy with bronchoalveolar lavage. An unusual subacute form of implementation of aspergillosis was confirmed by a bronchoalveolar lavage culture that showed the presence of Aspergillus . Images taken during bronchoscopy revealed Aspergillus implantation in the lung and serum galactomannan antigen test was positive. Voriconazole was introduced, 200 mg daily. The patient showed clinical improvement and was discharged from our hospital. We conclude that subacute invasive aspergillosis is a serious infection that can lead to high mortality. Bronchoscopy with bronchoalveolar lavage allows access and effective visualization of the airway as well as sampling for Aspergillus identification.